Relative Wage Variability in the United States 1860-1983 - Allen, Steven G. (The Review of Economics and Statistics, 1987)
This paper examines the magnitude of changes in relative wages across industries between 1860 and 1983 and analyzes the macroeconomic determinants of such changes at different intervals during this period. The variance across industries in wage growth was at least four times larger before 1948 than afterward. Except for smaller year-to-year variability in output growth across industries after 1948, the macroeconomic factors examined cannot account for this increased rigidity of relative wages. Increases in average establishment size and improved communication of wage trends are probably partially responsible for the observed increase in relative wage rigidity. No single macroeconomic model was consistent with the year-to-year fluctuations in relative wage rigidity in every historical period examined.